Accumulation of ofloxacin and tosufloxacin in fluoroquinolone-resistant E coli - Xia Pei-Yuan; Feng Ping; Zhong Li; Lv Xiao-Ju; Lei Bing-Jun (Acta Pharmacologica Sinica, 2016)
Aim: To make sure whether there is a difference in mechanism existed in the resistant E coli strains accumulated hydrophilic fluoroquinolone ofloxacin and hydrophobic fluoroquinoline tosufloxacin. Methods: Fluoroquinolone accumulation in bacteria and effect of active efflux were measured by fluorescence method. Analysis of outer membrane proteins was made by SDS-PAGE. E coli strains included JF701 and JF703 that are OmpC- or OmpF-deficient mutants of E coli K-12 respectively, and the susceptible strain Ecs and its in-vitro selected resistant strains R2, R256, and clinical resistant isolates R5, R6. Results: Ecs accumulated ofloxacin almost at the same concentration as JF701, but JF703 did about 1/2 of that lower than JF701. However, four resistant strains accumulated ofloxacin about 5 to 7-fold lower than those susceptible strains. On the other hand, there was no significant difference for the accumulation of tosufloxacin between fluoroquinolone-resistant and -susceptible strains. After addition of proton ionophore DNP for 5 min and 10 min, the accumulation of tosufloxacin slowly decreased in E coli strains, whereas the accumulation of ofloxacin was increased, especially in the resistant strains. A good relevance exists between the accumulation increment of ofloxacin and its MIC for each E coli strain after addition of DNP for 5 min and 10 min (r=0.9623 and 0.8006 respectively). Furthermore, both OmpF and OmpC in Ecs, OmpF-deficiency in R2, R256 and OmpC-deficiency in R5, R6 were observed. Conclusion: The accumulation of ofloxacin other than tosufloxacin could be reduced by OmpF-deficiency and active efflux, and the latter may be an important factor in the development of resistance to hydrophilic fluoroquinolone in E coli.